Peran Green Marketing dan Environmental Attitude dalam Meningkatkan Green Purchase Intention: Green Brand Image sebagai Mediasi dan Consumer Involvement sebagai Moderasi pada UMKM di Kota Medan - Silalahi, Ronaldo Gunawan; Rosita; Hendry; Edward, Yusuf Ronny (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
The purpose of this study was to analyze the effect of green marketing and environmental attitude on green purchase intention, both directly and through the mediation of green brand image and moderation of consumer involvement, in MSMEs in Medan City. This study used the partial least square method using 250 samples. The results showed that green price, green product, green place, green promotion, and environmental attitude had a positive and significant effect on green purchase intention, and each also had a significant effect on green brand image. Green brand image was proven to significantly increase green purchase intention, while consumer involvement also had a significant effect on green purchase intention. However, only the moderation of consumer involvement on the relationship between green product and green purchase intention was significant, while the moderation on the relationship between green price, green place, green promotion, and environmental attitude was not significant. In addition, all mediation relationships through green brand image between green marketing components and environmental attitude on green purchase intention were proven to be significant, confirming the important role of green brand image in shaping consumer purchase intention towards environmentally friendly products of MSMEs in Medan City. In conclusion, green marketing and environmental attitude have a significant effect on green purchase intention, both directly and through green brand image as a mediator, while consumer involvement only significantly moderates the relationship between green products and green purchase intention.